How Brand Image Affects Expected Quality, Perceived Quality, Perceived Value, and Patient Satisfaction and Their Effect on Attitudinal Loyalty and Behavior Loyalty (A Study Done in a Dentist in West Jakarta) - Annamaria Gabriela; Ferdi Antonio (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was intended to analyze how brand image affects expected quality, perceived quality, perceived value, and patient satisfaction and how they affect attitudinal loyalty and behavior loyalty on a dentist's patients. Methods: this is quantitative research with surveys and cross-sectional data. The subjects are public dentist patients in West Jakarta, 2021. The sample was taken using purposive sampling, from which 290 respondents were deemed fit for the criteria. The data was then gathered through an online questionnaire and used a Likert 1-5 scale. The data was analyzed with PLS-SEM method using SmartPLS™ 3.3. Findings: This research had 11 supported hypotheses with a T-statistic value of >1.645 and alpha 0.05, while one hypothesis was not supported. Brand image has a significant positive effect on expected quality, perceived value, and patient satisfaction, while its effect was not significant on perceived quality. Perceived value has a significant positive effect on patient satisfaction, and patient satisfaction itself was found to have a positive effect on attitudinal loyalty and behavior loyalty. Conclusions: Brand image has a vital part to play in affecting perceived value, which will then increase patient satisfaction from patients who went to the dentist. Furthermore, patient satisfaction fosters their loyalty to the dentist, both from attitudinal side and behavioral side.